Slow Stroke Back Massage Therapy to Reduce Acute Pain in Elderly with Hypertension: A Case Study - Safitri, Yessi Eka; Susumaningrum, Latifa Aini; Kurdi, Fahruddin; Basri, Achmad Ali (Jurnal Kesehatan Komunitas Indonesia, 2023)
Background: Hypertension causes increased vascularization of blood vessels to the brain. This condition will affect the pressure on the nerve fibers in the neck muscles, so that the patient will feel discomfort in the head and nape. The incidence of acute pain in hypertensive patients at the Babelan I Health Center in 2022, namely patients with hypertension who experience moderate acute pain (scale 4-6 NRS) is as many as 16 people (64%). Purpose: Knowing the application of SSBM therapy to reducing acute pain in the elderly with hypertension at Melati room in UPT PSTW (nursing home) Jember. Method: This final scientific work uses the case report method which describes the case of Mrs. J with acute pain nursing problems. Nursing care was provided comprehensively for 6 sessions with 10 minutes for each meeting from 29 September to 05 October 2022. Results: After being given nursing care with SSBM intervention, it was found that there was a decrease in the client's pain level in terms of decreased pain complaints, the average pain scale was from 4.7 NRS to 3.8 NRS, the average systolic blood pressure was 151.7 mmHg to 141 .7 mm Hg, and the average blood pressure was 96.7 mm Hg to 87.5 mm Hg. Conclusion: 6 sessions of SSBM therapy with a duration of 10 minutes can have a positive effect on acute pain problems. Health workers are expected to use SSBM therapy in combination with other non-pharmacological therapies to reduce scale pain.